HERDING BEHAVIOR IN VOLATILE MARKET REGIMES: AN IN-DEPTH ANALYSIS OF COINS, TOKENS, PANDEMIC, PENNY, AND PRICEY CRYPTOCURRENCIES - Rayenda Khresna, Brahmana; Muhammad Arsalan, Hashmi; Abdullah, -; Josephine Yau, Tan Hwang (UNIMAS Publisher, 2023)
This study comprehensively analyzes herding behavior in the cryptocurrency market. First, we conduct an in-depth investigation of herding behavior in the overall cryptocurrency market. Second, we form several groups of cryptocurrencies according to their characteristics and analyze whether each group behaves similarly in volatile market regimes. Third, we investigate whether herding existed in each cryptocurrency group before and during the COVID-19 pandemic. Using a sample of 227 cryptocurrencies constituting nearly 95% of market capitalization, we reveal that herding behavior was absent in the overall sample and sub-samples comprising cryptocurrency groups. Further, the anti-herding behavior implies a contrarian response to the crowd. This anti-herding can be explained from two views: rational behavior of taking profit from market irrationality and irrational behavior due to fear or recency bias.